Combined spinal-epidural block for labor analgesia. Comparative study with continuous epidural block - Braga,Angélica de Fátima de Assunção (2019)
Abstract Introduction: Lumbar epidural block is an effective and routinely used technique for labor pain relief, and the combined spinal-epidural block has the benefit of using lower doses of local anesthetics and rapid onset of analgesia. The objective of this study was to evaluate the effectiveness and safety of two anesthetic techniques: combined spinal-epidural block and continuous epidural block in pregnant women for labor analgesia. Methods: Eighty patients, ASA II and III, with cephalic presentation and cervical dilation between 5 and 6 cm, undergoing labor analgesia, allocated in two groups according to the anesthetic technique: combined spinal-epidural (GI) and continuous epidural (GII). Pain severity before the blockade, time to complete analgesia, degree of motor blockade, time to full cervical dilation, duration of the second stage of labor, pain severity during the 1st and 2nd stage of labor, type of delivery, use of oxytocin during labor, maternal cardiocirculatory and respiratory parameters and adverse events, and neonatal repercussions were recorded. Results: At the time of anesthesia, pain severity was similar in both groups. Pain relief was faster in GI (4.5 ± 1.5 min) when compared to GII (11.6 ± 4.6 min) p = 0.01; pain scores in the first and second stages of delivery were lower in GI (0.9 ± 0.3 and 1.8 ± 0.7, respectively) when compared to GII (1.9 ± 0.6 and 2.2 ± 0.5, respectively), with p = 0.01 only in the first stage of labor; there was need for local anesthetics supplementation in GII; there were more frequent spontaneous deliveries in GI (80% of patients) than in GII (50%) (p = 0.045) and more frequent use of instrumental (p = 0.03) in GII (12 patients) compared to GI (4 patients); the frequency of cesarean deliveries was significantly higher (p = 0.02) in Group II than in Group I, with 4 cases in GI and 8 cases in GII; absence of maternal cardiocirculatory and respiratory changes and neonatal repercussions; more frequent pruritus in GI (10 patients) and (0 patients in GII) (p = 0.02). Conclusion: The combined blockade proved to be effective with better quality of analgesia and greater comfort for pregnant women, constituting a good option for the practice of obstetric analgesia.